Neurobiology of social behavior : toward an understanding of the prosocial and antisocial brain - Numan, Michael (Elsevier : Academic Press, 2015)
Social neuroscience is a rapidly growing, interdisciplinary field which is devoted to understanding how social behavior is regulated by the brain, and how such behaviors in turn influence brain and biology. Existing volumes either fail to take a neurobiological approach or focus on one particular type of behavior, so the field is ripe for a comprehensive reference which draws cross-behavioral conclusions. This authored work will serve as the market's most comprehensive reference on the neurobiology of social behavior. The volume will offer an introduction to neural systems and genetics/epigenetics, followed by detailed study of a wide range of behaviors - aggression, sex and sexual differentiation, mating, parenting, social attachments, monogamy, empathy, cooperation, and altruism. Research findings on the neural basis of social behavior will be integrated across different levels of analysis, from molecular neurobiology to neural systems/behavioral neuroscience to fMRI imaging data on human social behavior. Chapters will cover research on both normal and abnormal behaviors, as well as developmental aspects.